Four Evangelists for leading Innovation – von Hayek, Schumpeter, Coase, von Thünen - Torsten André Pohl (Universität Witten/Herdecke, Fakultät für Wirtschaftswissenschaft, 2017)
Organic Growth is back on top of Executives' agendas: “Executives shouldn't underesti-mate the power of organic growth. It may take more time and effort to affect a company's size, but organic growth typically generates more value. A look at the share price perfor-mance of 550 US and European companies over 15 years reveals that for all levels of reve-nue growth, those with more organic growth generated higher shareholder returns than those whose growth relied more heavily on acquistions”. Innovation is at the heart of driving Organic Growth – “building new products, services or business models, continually allocating funds to areas of proven growth and improving core capabilities”...
Keywords: 330